Energy Barriers: Gate‐Controlled Energy Barrier at a Graphene/Molecular Semiconductor Junction (Adv. Funct. Mater. 20/2015). (May 2015) - Parui, Subir; Pietrobon, Luca; Ciudad, David; Vélez, Saül; Sun, Xiangnan; Casanova, Fèlix; Stoliar, Pablo; Hueso, Luis E.
Abstract : Graphene is an ideal candidate for the source electrode in a vertical organic field effect transistor as it has low density of states near the Dirac point and easy gate tunability of the Fermi‐level. On page 2972, S. Parui, L. Hueso, and team modulate the energy barrier at a graphene/molecular semiconductor (fullerene) junction by varying the gate electric field, thus opening a promising route toward molecular‐semiconductor based devices.